The influence of training and cadence on gross efficiency in young elite cyclists - Ballak, S. B.; de Koning, J. J.; Noordhof, D. A. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Background: Successful road cycling requires energy preservation for the last and decisive part of the race. Therefore, high cycling efficiency during the majority of the race increases the chance on a good result. Gross efficiency (GE), considered as a key determinant of cycling performance, is the ratio between mechanical power output and metabolic power input [1], expressed as a percentage. Cadence is a factor that influences GE [1], therefore, determining a cyclist` most efficient cadence and using this cadence during racing may preserve energy during the bulk of the race. As training status also influences GE [2], changes in training status during the season may result in an altered GE and most efficient cadence during submaximal cycling exercise. Currently, the change in GE and most efficient cadence have not been investigated in young elite athletes during the preparation phase of the season. Therefore, the goal of this study was to determine GE and the most efficient cadence during submaximal cycling exercise of a group of young elite cyclists in the winter and in the spring. Methods: To investigate GE and the most efficient cadence, respiratory data (Cosmed Quark CPET) were collected in six young elite male road cyclists (18.5±1.9 yrs), at five different cadences (70, 80, 90, 100, and 110 RPM), while cycling 6 min for each RPM at 4 W/kg (Lode, Excalibur Sport). Repeated measures ANOVA was used to determine differences in GE between cadences, while a post hoc analysis was then conducted to identify the significant differences between groups. Results: GE at 70 and 80 RPM (23.4±0.6 and 23.5±0.3 %) was significantly higher (p<0.05) than GE at 90, 100 and 110 RPM (22.7±0.4, 22.1±0.6 and 21.2±0.5 %). Four cyclists were most efficient at 80 RPM and two cyclists at 70 RPM. Although the data of the first testing period have been collected, the data of the second testing period (which consists of an identical testing day as the first and an additional day to determine VO2max using an incremental test) have to be collected in a few months` time. Conclusion: These talented young cyclists are almost as efficient as world-class cyclists [3].Whether GE and most efficient cadence change after a winter training period will be determined in the coming months.